Genotype by environment interaction in different birth seasons for weight at 240, 365 and 450 days of age in Tabapuã cattle - Sousa Júnior, Severino Cavalcante de; Diaz, Iara Del Pilar Solar [UNESP]; Santos, Karina Rodrigues dos; Sousa, José Ernandes Rufino de; Sarmento, José Lindenberg Rocha; Martins Filho, Raimundo (FapUNIFESP (SciELO), 2012)
The objective of this study was to evaluate the effect of genotype by environment interaction (GEI) on the weight of Tabapuã cattle at 240 (W240), 365 (W365) and 450 (W450) days of age. In total, 35,732 records of 8,458 Tabapuã animalswhich were born in the state of Bahia, Brazil, from 1975 to 2001, from 167 sires and 3,707 dams, were used. Two birth seasons were tested as for the environment effect: the dry (D) and rainy (R) ones. The covariance components were obtainedby a multiple-trait analysis using Bayesian inference, in which each trait was considered as being different in each season. Covariance components were estimated by software gibbs2f90. As for W240, the model was comprised of contemporary groups and cow age (in classes) as fixed effects; animal and maternal genetic additive, maternal permanent environmental and residual were considered as random effects. Concerning W365 and W450, the model included only the contemporary aged cow groups as fixed effects and the genetic additive and residual effects of the animal as the random ones. The GEI was assessed considering the genetic correlation, in which values below 0.80 indicated the presence of GEI. Regarding W365 and W450, the GEI was found in both seasons. As for post-weaning weight (W240), the effect of such interaction was not observed. ©2012 Sociedade Brasileira de Zootecnia.
Keywords: Bayesian inference; Beef cattle; Genetic correlation; Multiple-trait analysis